Magnetic stimulation at Neiguan (PC6) acupoint increases connections between cerebral cortex regions - Yu, Hong-li (Neural Regen Res, 2016)
Stimulation at specific acupoints can activate cortical regions in human subjects. Previous studies have mainly focused on a single brain region. However, the brain is a network and many brain regions participate in the same task. The study of a single brain region alone cannot clearly explain any brain-related issues. Therefore, for the present study, magnetic stimulation was used to stimulate the Neiguan (PC6) acupoint, and 32-channel electroencephalography data were recorded before and after stimulation. Brain functional networks were constructed based on electroencephalography data to determine the relationship between magnetic stimulation at the PC6 acupoint and cortical excitability. Results indicated that magnetic stimulation at the PC6 acupoint increased connections between cerebral cortex regions.